The early modern villa senses and perceptions versus materiality - Arciszewska, Barbara 1962-; Beaven, Lisa; Caldas, João Vieira 1953-; Cornaglia, Paolo; Frank, Martina 1956-; Frommel, Sabine 1958-; Ganofsky, Marine; Glória, Ana Celeste; Gonçalves, Ana Rita; Helprin, Alexandra; Jakubec, Ondřej 1976-; Jaskanis, Paweł 1958-; et al. (Museum of King Jan III's Palace at Wilanów, 2017)
Proceedings of the conference held on October 15th-17th 2014, at the Wilanów Palace Museum, Warszawa, Poland. The focus of the conference is to show the role of the senses and sensual perception in the planning, design, as well as functioning and reception of the villa (ca. 1450-1800) - set against the essential materiality of architecture and nature, understood as the framework of reference for the sensual experience rooted in pre-modern concepts of the corporeal sensorium. The conventional, Aristotelian five senses (sight, hearing, touch, smell, taste) often appeared in the allegorical disguise in decorations of early modern villas, indicating particular significance of these themes for suburban or country residences. Indeed, the villa and surrounding estate, combining nature and artifice, offered a perfect site for deploying diverse strategies of sensuality. The symposium aims to explore this sense-oriented villa culture from the point of view of the patron, artist/artisan as well as the audience, in their class and gender polarization. The articles examine how theory and practice of contemporary architectural and landscape design, as well as interior decoration and furnishings, offered ways of engaging sight, touch, or any other sense, by a myriad of means: colour, shape, texture etc. Case studies report new findings in the area of colour use in the early modern interiors. Papers discuss various attempts to bridge the gap between senses in the context of villa architecture and its fittings, facilities, machinery, accessories and garden structures, such as musical fountains, edible sculpture etc. Contributions demonstrate how the social ritual of the contemporary villeggiatura served as a means of sensual display
Based on papers given during the 2014 conference "The Early Modern Villa. Senses and Perceptions versus Materiality" held at the Museum of Kin Jan III's Palace at Wilanów
Keywords: Geschichte 1400-1800; Villa; Herrenhaus; Konferenzschrift -- 2014 -- Warschau; Aufsatzsammlung